2009
DOI: 10.1093/rpd/ncp095
|View full text |Cite
|
Sign up to set email alerts
|

Radioactivity in drilled and dug well drinking water of Ogun state Southwestern Nigeria and consequent dose estimates

Abstract: Activity concentrations of (40)K, (226)Ra, (228)Ac and (235)U were measured in 11 dug and 9 drilled well water samples from 3 large cities in Ogun state, Southwestern Nigeria, consumed by the population living in the cities. The measurement was done using co-axial type high-purity germanium (HPGe) detector (Canberra Industries Inc.). The measured activity concentrations in the water samples ranged from 1.74 +/- 1.83 to 4.69 +/- 0.17 Bq l(-1); 2.89 +/- 0.62 to 7.79 +/- 7.22 Bq l(-1); 0.35 +/- 0.07 to 1.17 +/- 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 15 publications
4
18
2
Order By: Relevance
“…This could again be attributed to geology formation of the study area and the various radionuclide induce activities of the exploration companies. These obtained values are higher than that reported by Ajayi et al, 2009) in drilled and hand dug well drinking water in Abeokuta, Ogun State and those reported by Yussuf et al, (2012) in drinking and mineral water in Johor Bahru, Malaysia. But these obtained values are lower than the values reported by Vesterbacka (2007) in drinking water in Finland.…”
Section: (6)contrasting
confidence: 64%
See 1 more Smart Citation
“…This could again be attributed to geology formation of the study area and the various radionuclide induce activities of the exploration companies. These obtained values are higher than that reported by Ajayi et al, 2009) in drilled and hand dug well drinking water in Abeokuta, Ogun State and those reported by Yussuf et al, (2012) in drinking and mineral water in Johor Bahru, Malaysia. But these obtained values are lower than the values reported by Vesterbacka (2007) in drinking water in Finland.…”
Section: (6)contrasting
confidence: 64%
“…The largest contribution of the overall activity concentration in all the various produced water samples come mainly form 40 K with the lowest concentration of 9.08 ± 4.75Bql -1 and the highest concentration being 155.2 ± 32.27Bql -1 . This relatively higher concentration of 40 K can be attributed to the presence of clay that characterized the formation in the Niger Delta and its abundance in the earth crust (Ajayi et al, 2009;Tchokossa et al, 1999). The specific activity concentration due to 228 Ra is relatively low in all the produced water samples investigated compared to 226 Ra, this is because 226 Ra is more mobile than 228 Ra (NCRP, 1987).The obtained average values exceeded the (WHO, 2008) standard values limit of 10Bql -1 , 1.0Bql -1 and 0.1Bql -1 for 40 K, 226 Ra and 228 Ra respectively, these are clearly shown graphically in figures 1-3.…”
Section: (6)mentioning
confidence: 99%
“…Also recently an annual effective dose rate of 1.64 mSv due to environmental radiation has been reported for the city [4]. Metal pollution in shallow well water samples in the neighboring town to the study areas has been reported [5], radioactivity in borehole water in neighboring state [6] and in part of Ogun State [7]. It is therefore envisaged that radionuclide concentrations may be elevated in the different food crops and the diets derivable from them.…”
Section: Introductionmentioning
confidence: 90%
“…The local economies in the Odeda and Obafemi-owode areas in Ogun State, Nigeria are characterized by agricultural and stone quarrying activities while, hand-dug wells, streams, and boreholes are the major sources of water for drinking and other domestic activities. Metal pollution has been reported in shallow well water samples in the neighboring town, Ago-Iwoye has been reported [1], and radioactivity has been detected in borehole water in a neighboring state [3] and in part of Ogun state [4]. Furthermore, baseline studies of terrestrial outdoor gamma dose rate levels in Nigeria have shown that the areas under investigation exhibited high concentrations of terrestrial radionuclides [5,6].…”
Section: Introductionmentioning
confidence: 99%